Gorillas in danger - Orme, Helen (New York : Bearport Pub., 2007)
Reveals how the world's gorilla population is being threatened by poachers and the destruction of their natural habitats and describes how various groups are trying to save the gorillas from becoming extinct.
Rare animals -- Young mountain gorillas -- Families -- Looking for food -- Difficult times -- More troubles -- Poachers -- People who help -- Visiting the gorillas -- Surviving.
Includes index.
5.6
3-6
Keywords: Gorilla -- Juvenile literature; Gorilla; Gorillas